Fabrication of CNT as transparent electrode of large-area electronic devices - Lim, Yu Han. (2009)
As the need to develop high power conversion efficiency (PCE) and low cost photovoltaic (PV) cell, organic PV (OPV) has seen growing research interest in recent years. One of the most important components of the OPV is the transparent conductive electrode, necessary for light transmission into the absorber materials. The most commonly used transparent electrode to date, Indium tin oxide (ITO), may not be suitable for some OPV devices on flexible substrates. High conductivity at a relatively high transparency level offered by singlewalled carbon nanotubes (SWNT), coupled with its good resistance to creep, crack and strain, makes it a front-runner of ITO replacement for flexible OPV devices. This project aims to investigate the feasibility of using SWNT as a transparent electrode. This project was investigated based on 2 main parts, (1) CNT layer deposition and (2) OPV device fabrication. The effects of various parameters of 2 types of CNT deposition methods – transfer printing and spray coating were investigated. PV cells made of transfer printed SWNTglass and sprayed coated SWNT-glass were also compared. The results show that an optimum combination of sonication power and CNT concentration is required to obtain a low sheet resistance (Rs) of 300 -1 at 80% transparency, comparable to the best-reported condition in literature. Spraying was also found to be a better deposition method in terms of uniformity, Rs and roughness. An OPV device was successfully fabricated using spray-coated CNT electrode, although further optimization of device fabrication is necessary to improve the PCE. In conclusion, this study found that CNT is a feasible alternative for ITO when Rs and roughness are optimized to a lower value to maximize its performance in a PV cell.